Integrated life cycle and data envelopment analysis of input optimization and environmental impacts in silage corn farming - Amir Azizpanah; Majid Namdari; Alaa Kamil Abed (Results in Engineering, 2025)
This study addresses the critical challenge of unsustainable silage corn (Zea mays L.) production by integrating Life Cycle Assessment (LCA) and Data Envelopment Analysis (DEA). Focusing on 31 farms in Dehloran County, Iran, our unique methodological combination allowed for comprehensive energy efficiency assessment, input optimization, and environmental impact quantification. This approach specifically identifies opportunities for improved sustainability by linking operational inefficiencies to environmental burdens. Initial findings revealed high energy consumption (84,766.00 MJ ha-1), dominated by electricity, diesel, and nitrogen fertilizers. DEA showed that 54.38 % of farms were efficient, with inefficient ones capable of a 14.45 % input reduction, equating to 9294.85 MJ ha-1 energy savings. Critically, LCA demonstrated significant environmental benefits post-optimization, with reductions in key impact categories: respiratory inorganics (10.82 %), terrestrial ecotoxicity (10.81 %), and global warming potential (9.51 %). Endpoint impacts on human health, ecosystem quality, and climate change also improved. These results highlight the powerful synergy of LCA-DEA in providing actionable insights for sustainable agriculture. We advocate for precision agriculture, renewable energy adoption, and optimized fertilizer use to enhance resource efficiency and significantly reduce the environmental footprint of silage corn production, offering a replicable framework for similar agricultural systems.